Third-generation antivenomics analysis of the preclinical efficacy of Bothrofav® antivenom towards Bothrops lanceolatus venom. (January 2019) - Pla, Davinia; Rodríguez, Yania; Resiere, Dabor; Mehdaoui, Hossein; Gutiérrez, José María; Calvete, Juan J.
Abstract: Bothrops lanceolatus inflicts severe envenomings in the Lesser Caribbean island of Martinique. Bothrofav®, a monospecific antivenom against B. lanceolatus venom, has proven highly effective at the preclinical and clinical levels. Here, we report a detailed third-generation antivenomics quantitative analysis of Bothrofav®. With the exception of poorly-immunogenic peptides, Bothrofav® immunocaptured all the major protein components. These results, along with previous preclinical and clinical observations, underscore the high neutralizing efficacy of the antivenom against B. lanceolatus venom. Graphical abstract: Image 1 Highlights: The immunoreactivity of the monospecific antivenom Bothrofav® was evaluated against Bothrops lanceolatus venom. Third Generation Antivenomics approach was used in this study. Antivenom immunocaptured all major venom components. Results agree with previous preclinical studies and demonstrate the efficacy of this antivenom.